Promoting the multifunctionality of agriculture, forestry, and rural areas - design and implementation of public policies in Germany - Paul Lehmann; Christian Schleyer; Henry Wüstemann; Martin Drechsler; Konrad Hagedorn; Frank Wätzold (UFZ-Umweltforschungszentrum Leipzig-Halle, 2005)
The multiple roles and functions of agriculture and forestry beyond those of supplying food and fibre, such as the provision of environmental benefits and the contribution to the socio-economic viability of rural areas, account for a growing recognition in both scientific debates and political decision making. In order to foster further research in the field of multifunctionality of agriculture, forestry, and rural areas, this report provides an overview of the scientific work that has been done with respect to the different ways and goals of setting up and management of public policies with multifunctional purpose. It particularly focuses on policies that have been implemented in Germany since 1992. Initially, a description of traditional policies for multifunctionality that have been initiated at EU, national, Laender, regional, and local level is provided. This includes, among other things, the EU Rural Development Regulations, the LEADER initiatives, the Flora-Fauna-Habitats Directive and Federal State and Laender legislation on protected areas. For each policy presented, apart from their content, important characteristics with regard to their setting up and implementation, such as responsibilities for and processes of goal determination, policy and measure design, and administrative implementation are presented. Subsequently, policies are introduced that particularly aim at creating new markets and services. Furthermore, innovative approaches are presented which involve new institutional arrangements for the provision of goods and services. Based on this presentation, the scientific debate on the design and implementation of policies with multifunctional purpose is sketched out. Five major strands of debates dealing with issues of setting up and management of those policies are highlighted: First, scientific literature is reflected that discusses issues regarding the allocation of property rights and the related question of applying standards, such as GFP, or incentive based policies. Second, light is shed on the scientific debate on the appropriate degree of centralisation and decentralisation, respectively. Third, directions of the discussion on policy and scheme design are considered. Fourth, the closely related issues of acceptance and demand of policies are highlighted. Fifth, questions of monitoring and enforcement are addressed. Finally, the main research gaps are highlighted. Outstanding and promising issues include the research on optimal institutional arrangements of property rights and matching forms of governance as well as interdisciplinary work on policies other than agri-environmental schemes.
Keywords: Q18; Q28; 330; Multifunctionality; agricultural policy; rural area; agri-environmental policies; Germany; review